What Factors Do Customers Consider Before Deciding To Open A Bank Account? (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study is to determine how bank personnel’ communication and understanding, as well as the telemarketing strategies used by banks, can affect consumers’ decisions to open accounts. The study’s participants were patrons of both commercial and state-owned banks (X and Y). 205 participants made up the sample that was gathered through incidental sampling. Questionnaires were distributed between November and December of 2023. The SmartPLS data analysis approach was applied. The findings demonstrate that the three independent research variables—communication, knowledge, and telemarketing—have an impact on consumers’ decisions to open bank accounts. By concentrating on this, the company will be able to increase sales and long-term business growth, especially in the area of acquiring new customers.